Identifying Stocks of better managed U.S. Banks : A Combined Fundamental and Technical Analysis of the S&P 500 - Kotomkin, Viktor; Ali, Tanweer; Rosecká, Nikola; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
The bachelor`s thesis aims to identify stocks of better-managed U.S. banks with the most growth potential. It is done by conducting fundamental and technical analysis in 2023 and evaluating the price of chosen stocks in 2024. The thesis describes macroeconomic factors, fundamental ratios, price ratios and technical indicators that drive the banking sector and stock price. Afterwards, four hypotheses about the impact of variables on stock growth are tested practically using different statistical methods such as correlation, multiple regression and t-test analyses. Further, it is concluded what exact factors, ratios and indicators should be used for such analysis and what stocks with the most growth potential are identified. The results provide valuable insights for retail investors about the most relevant variables that affect stock price growth and a simplified approach to investing in the banking sector.
Vedoucí práce: Tanweer Ali
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses